Hagiography as a Macrogenre - Požin, Karin (Slavia Centralis, 2023)
Within the framework of the social-semiotic approach of the Sydney School (Martin and Rose 2008), this paper examines the genre characteristics of selected short descriptive narrative hagiographic texts published in three prominent Slovene hagiographic collections from 19th century – Shivlenje Svetnikov in Prestavni Godovi (1828–1829) by Franc Veriti, Djanje Svetnikov Božjih in razlaganje prestavnih praznikov ali svetkov (1853–1854) by Anton Martin Slomšek, and Življenje svetnikov in svetnic Božjih (1866–1874) by Jožef Rogač and Matija Torkar. Through a multi-level analysis, the study reveals the macrostructural textual organization, identifies both mandatory and optional structural segments, defines contextual variables and the appraisal system. This confirms the social purpose of the examined hagiographies, which is to provide significance and convey Christian principles by presenting the life of holy individuals, with the intention of preserving and shaping relationships on both broader and narrower social levels.
Keywords: systemic-functional linguistics, genre theory, Sydney School, macrogenre, slovene hagiography, 19th century